New opportunities in mesothelioma - Chudzik, Robert; Jarosz, Katarzyna; Gołębiowska, Maria; Gołębiowska, Beata; Szafraniec, Aneta (Journal of Education, Health and Sport, 2017)
Mesothelioma is one of the most malignant neoplasms affecting the thin lining of the body's internal organs, known as the mesothelium. Asbestos is considered as the main etiological factor,but other substances such as natural mineral fibers (nickel, beryllium, silica dust), ionizing radiation, some organic compounds and SV40 virus are also recognized as carcinogens in this disease. The peak incidence of mesothelioma falls after the age of 60 and and the incidence among the male population is higher than in female (approximately 9:1). The aim of the study was to show to new possibilities in the diagnosis and treatment of pleural mesothelioma. For this purpose, the authors analized the latest articles (2016-2017) from the pubmed database. Numerous research studies show the development of treatment options, particularly in the field of immunotherapy, but also in the improvement of radiotherapy and chemotherapy. It is difficult to talk about radical surgery because of the specificity of the disease, so decided to work on intraoperative chemotherapy. Due to the poor prognosis of mesothelioma, palliative treatment is also important. However, the amount of asbestos remained among us, which we still have contact with, may influence to further increase the incidence of mesothelioma. Current literature shows us that promising works on new diagnostic and therapeutic options for mesothelioma are conducted.